2008
DOI: 10.1098/rsta.2008.0002
|View full text |Cite
|
Sign up to set email alerts
|

Wake attenuation in large Reynolds number dispersed two-phase flows

Abstract: The dynamics of high Reynolds number-dispersed two-phase flow strongly depends on the wakes generated behind the moving bodies that constitute the dispersed phase. The length of these wakes is considerably reduced compared with those developing behind isolated bodies. In this paper, this wake attenuation is studied from several complementary experimental investigations with the aim of determining how it depends on the body Reynolds number and the volume fraction a. It is first shown that the wakes inside a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 16 publications
5
54
1
Order By: Relevance
“…At this stage, it is important to recall that the wake of a sphere surrounded by many spheres is strongly attenuated compared to that of an isolated sphere, as is the case for a bubble in a swarm of bubbles (Risso & Ellingsen 2002;Roig & Larue de Tournemine 2007). Risso et al (2008) have shown that both the wake of a sphere or the wake of a bubble exponentially decay with the distance, and have almost vanished before 3 diameters. Spatial fluctuations are therefore dominant at scales comparable or larger than d ≈ Λ.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At this stage, it is important to recall that the wake of a sphere surrounded by many spheres is strongly attenuated compared to that of an isolated sphere, as is the case for a bubble in a swarm of bubbles (Risso & Ellingsen 2002;Roig & Larue de Tournemine 2007). Risso et al (2008) have shown that both the wake of a sphere or the wake of a bubble exponentially decay with the distance, and have almost vanished before 3 diameters. Spatial fluctuations are therefore dominant at scales comparable or larger than d ≈ Λ.…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated by the fact that, at the same Reynolds number, the drag coefficient of a bubble is much smaller than that of a solid sphere. Nonetheless, the wake of a bubble in a swarm of bubbles and that of a solid sphere in a swarm of spheres both exponentially decrease with the distance, and differ from each other only by their length of decay (Risso et al 2008). At same α and Re, the fluctuations generated by an array of spheres will have different magnitudes and length scales than those of a swarm of bubbles.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations